Effect of Ring Size on Acid Dichromate Oxidation of Alicyclic Ketoximes: A Kinetic Study - Janibai, T.S.; Usha, V.; Subbalakshmi, R. (Asian Journal of Chemistry, 2016)
Kinetics of oxidation of three alicyclic ketoximes by acid dichromate have been studied in aqueous acetic acid medium. The oxidation of alicyclic ketoximes by acid dichromate is first order each in [oxidant] and [substrate]. The reactions are acid-catalyzed. The negligible effect of the added perchlorate and the decrease in rate constants with decreasing dielectric strength of the medium indicate that the reaction involves ion-dipole interaction. The rate data have been measured at different temperatures and the activation parameters computed. Based on the kinetic results obtained, a plausible mechanism is proposed. Among the alicyclic ketoximes the reactivity sequence observed is cyclohexanone oxime (ChexO) > cyclopentanone oxime (CPO) > cycloheptanone oxime (ChepO). This trent is rationalized in the light of I-strain.